The Impact of Childhood and Parental Vaccination on SARS-CoV-2 Infection Rates in Children. Issue 10 (28th June 2022) - Yigit, Metin; Ince, Yunus Emre; Kalayci, Furkan; Santaflioglu, Beytullah; Kurt, Funda; Ozkaya-Parlakay, Aslinur; Dibek Misirlioglu, Emine; Senel, Emrah
Abstract : Background: The data on the indirect protection of children via the coronavirus disease 2019 (COVID-19) vaccination of household members are insufficient, and analyses to evaluate the efficacy of COVID-19 vaccines are limited. Methods: We gathered data on 12, 442 patients under the age of 18 regarding the vaccination status of their household members, their vaccine preferences and doses, and their previous history of COVID-19 infection immediately before the patients were administered a real-time reverse transcriptase-polymerase chain reaction (RT-PCR) test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) between September 1, 2021 and December 5, 2021. Results: A total of 18.4% (2289) were vaccinated, 91.4% with BNT162b2mRNA vaccine, 8.6% with inactivated COVID-19 vaccine; 48.7% received a single dose, and 51.3% had 2 doses. Real-time RT-PCR positivity proportions were much higher in older children ( P < 0.001) and were higher in children 12 years of age and older [odds ratio (OR), 1.34; 95% confidence interval (CI): 1.21–1.47] compared with others. SARS-CoV-2 infection was significantly lower in the vaccinated group (fully and incompletely) ( P < 0.001). Unvaccinated (OR, 4.88; 95% CI: 3.77–6.13) and incompletely vaccinated children (OR, 1.83; 95% CI: 1.52–2.12) had a higher risk of COVID-19 infection compared with fully vaccinated patients No significant association was found between the COVID-19 real-time RT-PCR positivity rates of patients and the vaccination status or vaccine preferences of household members ( P > 0.05 each). Conclusions: SARS-CoV-2 infection rates were significantly lower in vaccinated children, especially with mRNA vaccines. The indirect protection of unvaccinated children via the vaccination of household members against COVID-19 seems inadequate. The individual vaccination of children remains crucial.